Optimalisasi Cash Waqf Linked Sukuk (CWLS) Melalui Peningkatan Literasi Wakaf (Studi Pada Wakaf Salman ITB) - Khairani, Isti; Karamy, Nabiel; Didjaya Prawinata, Raden Bhatara; Saripudin, Udin; Handri, Handri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
This research aims to analyze the optimization of Cash Waqf Linked Sukuk (CWLS) which is already underway. Until the end of 2022 in Retail CWLS series SWR 001 in 2020, CWLS Retail series SWR 002 in 2021, and CWLS Retail series SWR 003 in 2022. The research was conducted using descriptive methods with the research object at Wakaf Salman ITB as nazhir or manager waqf. The research results show that Waqf Salman has taken strategic steps in collaboration with various stakeholders. In increasing cash waqf through CWLS, it is necessary to increase education regarding sharia financial literacy and waqf literacy as well as knowledge about CWLS products. Education can be carried out through social media or webinars which further educate the advantages of CWLS products which have many benefits, not only for wakif, mauquf alaih, but also for the development of the sharia economy and national development.